The Role of Nahwu and Sharf Sciences in Arabic Language Learning - Ismi Nujaima; Hendra Kurniawan (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
Language is a tool for thinking, expressing and communicating. One of the basic competency development areas in kindergarten is language development. Language allows children to translate experiences into symbols that they can use to communicate and think. The study of sharaf or Arabic morphology is about word forms. In Arabic, syntax is known as nahwu. Sharif (2017:97) says,